Appréhender et s’adapter - Clément Garineaud (Revue d'ethnoécologie)
Brittany's coastline has an exceptional diversity of algae, which is nowadays impacted by climate change, thus affecting the harvesting activities that have been carried out for several centuries. The seaweeds harvesters who collect the algae are directly concerned and they are also privileged observers. Based on ethnographic and ethnoecological material, this article examines the local knowledge, the perception of changes and their articulation with climates changes. The seaweeds harvesters have developed a rich and complex local knowledge that hels them predict and harvest the resource, taking into account its variability. Though the apprehension of climate change was low among harvesters, this knowledge appears as an indicator of local changes. The exceptional climatic hazard in 2014, a potential outline of the upcoming change, has revealed the adaptive capacity, in the short term, of professionals, producing new know-how and knowledge. One of the transformations is the intensification of interactions between scientific actors and harvesters with the development of hybrid knowledge. Although the knowledge-based approach provides precise information on the reality of climate change among seaweeds harvesters, it is constrained to understand all transformations, particularly in governance, and to enable the realization of a holistic anthropology of climate change.